Reducing the occurrence of shivering with intravenous dexmedetomidine in patients undergoing caesarean delivery under spinal anaesthesia : a double-blinded, randomised controlled trial of the efficacy and safety - Adnan, Wan Ahmad Asyraf Wan Md (2019)
Background Shivering is a very discomforting experience following spinal anaesthesia, especially in patients undergoing caesarean delivery. The objective of this study was to investigate the efficacy and safety of intravenous (IV) dexmedetomidine in preventing shivering in patients undergoing caesarean delivery under spinal anaesthesia. Methods This was a prospective, double-blind, randomized trial involving 62 parturients undergoing caesarean delivery under spinal anaesthesia. They were divided into 2 groups; patients in group D (dexmedetomidine, n = 31) received 0.5mcg/kg IV dexmedetomidine over 10 minutes followed by infusion of 0.4mcg/kg/hr until end of surgery; whilst patients in group C (saline, n = 31) received equivalent loading and infusion volume of 0.9% saline. The occurrence of shivering, sedation score and haemodynamic parameters were recorded intraoperatively. Results The occurrence of shivering was significantly reduced in group D as compared to group C (3.2% vs 64.5%, p < 0.001). Patients in group D were more sedated as compared to group C (51.6% vs 0%, p < 0.001). There were no statistically significant difference in systolic and diastolic blood pressure between both groups. Heart rate in group D were significantly lower than group C but still within normal physiological range. Conclusion IV dexmedetomidine was effective in reducing the occurrence of shivering but with significant sedative effect and lowering of heart rate than placebo. However, the value of heart rate was still within normal range.